2021
DOI: 10.1152/ajpheart.00366.2020
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1-mediated deacetylation of NF-κB inhibits the MLCK/MLC2 pathway and the expression of ET-1, thus alleviating the development of coronary artery spasm

Abstract: Coronary artery spasm (CAS) is an intense vasoconstriction of coronary arteries that cause total or subtotal vessel occlusion. The cardioprotective effect of sirtuin-1 (SIRT1) has been extensively highlighted in coronary artery diseases. The aims within this study include the investigation of the molecular mechanism by which SIRT1 alleviates CAS. SIRT1 expression was first determined by RT-qPCR and Western blot analysis in an endothelin-1 (ET-1)-induced rat CAS model. Interaction among SIRT1, nuclear factor-ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Absent in melanoma 2 (AIM2) restrains the acetylation of NF-κB by interacting with signal transducer and activator of transcription 1 (STAT1) phosphorylation, thereby reducing the transcription of inflammatory factors in cardiac myocytes [ 51 ]. In addition, Sirt1-mediated NF-κB deacetylation hinders the myosin light-chain kinase/myosin light chain-2 (MLCK/MLC2) pathway and endothelin-1 (ET-1) expression, thus alleviating coronary artery spasm [ 52 ]. Pterostilbene (PTE) abates NF-κB acetylation in BV-2 microglia through up-regulation of Sirt1, thereby choking the expression of inflammatory factors [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absent in melanoma 2 (AIM2) restrains the acetylation of NF-κB by interacting with signal transducer and activator of transcription 1 (STAT1) phosphorylation, thereby reducing the transcription of inflammatory factors in cardiac myocytes [ 51 ]. In addition, Sirt1-mediated NF-κB deacetylation hinders the myosin light-chain kinase/myosin light chain-2 (MLCK/MLC2) pathway and endothelin-1 (ET-1) expression, thus alleviating coronary artery spasm [ 52 ]. Pterostilbene (PTE) abates NF-κB acetylation in BV-2 microglia through up-regulation of Sirt1, thereby choking the expression of inflammatory factors [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, both the RhoA/LIMK2/cofolin and RhoA/MLCK pathways can lead to cell contraction [ 15 , 24 ]. Our results demonstrated that Ang II exposure significantly activated the RhoA/LIMK2/cofilin and RhoA/MLCK signaling pathways, manifested as an increase in key molecules, such as p-LIMK2, p-cofilin and MLCK, which was reversed by propofol and Rhosin (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Activated RhoA can stimulate LIMK2 and cofilin phosphorylation,inhibit the degradation of the F-actin cytoskeleton and lead to stable cell contraction [ 15 ]. RhoA activation also inhibits the function of myosin light chain phosphatase, which is responsible for the dephosphorylation of MLC2, and thus keeps MLC2 phosphorylated [ 24 ]. In addition, the interaction between actin and myosin is implicated in vasoconstriction [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that SIRT1 is involved in deacetylation of NF-κB and inhibition of NF-κB activation. 21 , 22 Next, we checked whether bergamottin could promote SIRT1 expression to inhibit NF-κB signaling. LPS stimulation decreased the mRNA level of SIRT1 in the lung tissues of mice ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%